9+11a=-5a+12

Simple and best practice solution for 9+11a=-5a+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9+11a=-5a+12 equation:


Simplifying
9 + 11a = -5a + 12

Reorder the terms:
9 + 11a = 12 + -5a

Solving
9 + 11a = 12 + -5a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '5a' to each side of the equation.
9 + 11a + 5a = 12 + -5a + 5a

Combine like terms: 11a + 5a = 16a
9 + 16a = 12 + -5a + 5a

Combine like terms: -5a + 5a = 0
9 + 16a = 12 + 0
9 + 16a = 12

Add '-9' to each side of the equation.
9 + -9 + 16a = 12 + -9

Combine like terms: 9 + -9 = 0
0 + 16a = 12 + -9
16a = 12 + -9

Combine like terms: 12 + -9 = 3
16a = 3

Divide each side by '16'.
a = 0.1875

Simplifying
a = 0.1875

See similar equations:

| (3n+1)-(5n+(-7))= | | n+137=-2n-4 | | 4d-5=0 | | 4y+(y+35)=180 | | p(x)=(x-(2-3i))(x-(2+3i)) | | 0=12x^2-40x-32 | | (-7n+(-3))-(-9n+5)= | | 18m-14=18m+18+2m | | -6+4=14y-10-13y | | 25/5(2+3)=25 | | 8n-9=n+285 | | (-9n+4)-(-2n+(-5))= | | 2abs(x-15)+abs(15-x)=27 | | 25/5(2+3)=1 | | (5n+4)-(6n+(-2))= | | -4b+7=b+212 | | 8x+3(3x)=68 | | -9z+12=10z+12+4z | | 12(14z-11)= | | (2x+4)+(2x+2)=4(x-1)+8 | | Y-1=-x-3 | | =3x+7 | | -5-2x=-(-x-1) | | -2x+6-2x=-4x+6 | | 4t+3t-t+17=8+-3 | | x^2+4x+4=121 | | 7t(t-16)=0 | | 4+13g=17+4g+10g | | (8n+8)-(9n+3)= | | (3-w)(2w-1)=0 | | (n+7)-(6n+(-2))= | | a+238=-5a+4 |

Equations solver categories